Human c-myc onc gene is located on the region of chromosome 8 that is translocated in Burkitt lymphoma cells. - Dalla-Favera, R (1982)
Human sequences related to the transforming gene (v-myc) of avian myelocytomatosis virus (MC29) are represented by at least one gene and several related sequences that may represent pseudogenes. By using a DNA probe that is specific for the complete gene (c-myc), different somatic cell hybrids possessing varying numbers of human chromosomes were analyzed by the Southern blotting technique. The results indicate that the human c-myc gene is located on chromosome 8. The analysis of hybrids between rodent cells and human Burkitt lymphoma cells, which carry a reciprocal translocation between chromosomes 8 and 14, allowed the mapping of the human c-myc gene on region (q24 leads to qter) of chromosome 8. This chromosomal region is translocated to either human chromosome 2, 14, or 22 in Burkitt lymphoma cells.